Differences in Risk Behavior and Demographic Factors Between Men Who Have Sex With Men With Acute and Nonacute Human Immunodeficiency Virus Infection in a Community-Based Testing Program in Los Angeles. (1st April 2017) - Joseph Davey, Dvora; Beymer, Matthew; Roberts, Chelsea P.; Bolan, Robert K.; Klausner, Jeffrey D.
Abstract : Introduction: High viremia combined with HIV-infection status unawareness and increased sexual risk behavior contributes to a disproportionate amount of new HIV infections. Methods: From August 2011 to July 2015, the Los Angeles Lesbian, Gay, Bisexual, and Transgender Center conducted 66, 546 HIV tests. We compared factors, including the presence of concomitant sexually transmitted infections, number of recent sex partners and reported condomless anal intercourse between men who have sex with men (MSM) diagnosed with an acute HIV infection and a nonacute HIV infection using multivariable logistic regression. Results: Of 1082 unique MSM who tested HIV-infected for the first time, 165 (15%) had an acute infection and 917 had a nonacute infection. HIV rapid antibody testing was 84.8% sensitive for detecting HIV infection (95% confidence interval (CI): 82.9% to 87.1%). Median HIV viral load among acutely infected MSM was 842, 000 copies per milliliter (interquartile range = 98, 200–4, 897, 318). MSM with acute infection had twice the number of sex partners in the prior 30 days (median = 2) and prior 3 months (median = 4) before diagnosis compared with those diagnosed with nonacute infection ( P ⩽ 0.0001). The odds of acute HIV infection were increased with the numbers of recent sex partners after controlling for age and race/ethnicity (adjusted odds ratio (aOR) >5 partners in past 30 days = 2.74; 95% CI: 1.46 to 5.14; aOR >10 partners in past 3 months = 2.41; 95% CI: 1.36 to 4.25). Non-African American MSM had almost double the odds of being diagnosed with an acute HIV infection compared with African American MSM (aOR = 1.97; 95% CI: 1.10 to 3.52). Conclusions: MSM with acute HIV infection had nearly twice as many sex partners in the past 30 days and 3 months compared with MSM with newly diagnosed nonacute HIV infection. Those diagnosed with acute HIV infection had decreased odds of being African American MSM.